Cardiac Fibrosis in the Pressure Overloaded Left and Right Ventricle as a Therapeutic Target - Schimmel, Katharina; Ichimura, Kenzo; Reddy, Sushma; Haddad, Francois; Spiekerkoetter, Edda (Frontiers in Cardiovascular Medicine, 2022)
Myocardial fibrosis is a remodeling process of the extracellular matrix (ECM) following cardiac stress. “Replacement fibrosis” is a term used to describe wound healing in the acute phase of an injury, such as myocardial infarction. In striking contrast, ECM remodeling following chronic pressure overload insidiously develops over time as “reactive fibrosis” leading to diffuse interstitial and perivascular collagen deposition that continuously perturbs the function of the left (L) or the right ventricle (RV). Examples for pressure-overload conditions resulting in reactive fibrosis in the LV are systemic hypertension or aortic stenosis, whereas pulmonary arterial hypertension (PAH) or congenital heart disease with right sided obstructive lesions such as pulmonary stenosis result in RV reactive fibrosis. In-depth phenotyping of cardiac fibrosis has made it increasingly clear that both forms, replacement and reactive fibrosis co-exist in various etiologies of heart failure. While the role of fibrosis in the pathogenesis of RV heart failure needs further assessment, reactive fibrosis in the LV is a pathological hallmark of adverse cardiac remodeling that is correlated with or potentially might even drive both development and progression of heart failure (HF). Further, LV reactive fibrosis predicts adverse outcome in various myocardial diseases and contributes to arrhythmias. The ability to effectively block pathological ECM remodeling of the LV is therefore an important medical need. At a cellular level, the cardiac fibroblast takes center stage in reactive fibrotic remodeling of the heart. Activation and proliferation of endogenous fibroblast populations are the major source of synthesis, secretion, and deposition of collagens in response to a variety of stimuli. Enzymes residing in the ECM are responsible for collagen maturation and cross-linking. Highly cross-linked type I collagen stiffens the ventricles and predominates over more elastic type III collagen in pressure-overloaded conditions. Research has attempted to identify pro-fibrotic drivers causing fibrotic remodeling. Single key factors such as Transforming Growth Factor β (TGFβ) have been described and subsequently targeted to test their usefulness in inhibiting fibrosis in cultured fibroblasts of the ventricles, and in animal models of cardiac fibrosis. More recently, modulation of phenotypic behaviors like inhibition of proliferating fibroblasts has emerged as a strategy to reduce pathogenic cardiac fibroblast numbers in the heart. Some studies targeting LV reactive fibrosis as outlined above have successfully led to improvements of cardiac structure and function in relevant animal models. For the RV, fibrosis research is needed to better understand the evolution and roles of fibrosis in RV failure. RV fibrosis is seen as an integral part of RV remodeling and presents at varying degrees in patients with PAH and animal models replicating the disease of RV afterload. The extent to which ECM remodeling impacts RV function and thus patient survival is less clear. In this review, we describe differences as well as common characteristics and key players in ECM remodeling of the LV vs. the RV in response to pressure overload. We review pre-clinical studies assessing the effect of anti-fibrotic drug candidates on LV and RV function and their premise for clinical testing. Finally, we discuss the mode of action, safety and efficacy of anti-fibrotic drugs currently tested for the treatment of left HF in clinical trials, which might guide development of new approaches to target right heart failure. We touch upon important considerations and knowledge gaps to be addressed for future clinical testing of anti-fibrotic cardiac therapies.